MUET seminar 2022 second session / Nazima Versay Kudus - Kudus, Nazima Versay (Academy of Language Studies, 2023)
For the past three years, MUET seminars have been conducted virtually to adhere to COVID-19 restrictions and this year, the seminar was finally conducted face-to-face. This time around, the Majlis Perwakilan Pelajar, Universiti Teknologi MARA (UiTM) Cawangan Pulau Pinang with the collaboration of the MUET Unit invited a speaker from the Sultan Ahmad Shah Pahang Islamic University (UniPSAS), Pahang. Madam Shafinas Sharifuddin is a MUET Master Trainer. She has conducted MUET seminars in schools and at various universities. The 2-day seminar was held at the Dewan Seminar, UiTM Cawangan Pulau Pinang from 1 - 2 October 2022. A total of 160 MUET candidates from the Permatang Pauh Campus attended the session. Being an experienced MUET instructor, Madam Shafinas exposed the students to important skills and strategies to attempt the written paper (listening, reading and writing). Participants were excited to attend a live seminar where they could be involved more effectively. The speaking webinar was conducted online on 9 October to accommodate those sitting for the Session 3 Speaking test which commenced on 11 October 2022.